2008
DOI: 10.1017/s0022215108001710
|View full text |Cite
|
Sign up to set email alerts
|

Primary tracheal tumours: 21 years of experience at Peking Union Medical College, Beijing, China

Abstract: Objectives: To review our experience of the treatment of primary tracheal tumours.Study design: All medical notes of patients with primary tracheal tumours diagnosed between 1981 and 2002 were retrospectively analysed.Results: In this period, 80 patients were diagnosed with primary tracheal malignancy, 48 males and 32 females. The median age was 48 years. Sixty-nine patients had malignant tumours, most commonly adenoid cystic carcinoma (50.7 per cent) or squamous cell carcinoma (30.4 per cent). Fifty-five pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…The location of the tumor, which has rarely been studied in previous reports, seems to have significant prognostic value. In our study, malignant PTTs were mainly located in the upper and lower third of the trachea, which is in agreement with previous reports ( 13 ). The location of tumors might play a role in the prognosis.…”
Section: Discussionsupporting
confidence: 94%
“…The location of the tumor, which has rarely been studied in previous reports, seems to have significant prognostic value. In our study, malignant PTTs were mainly located in the upper and lower third of the trachea, which is in agreement with previous reports ( 13 ). The location of tumors might play a role in the prognosis.…”
Section: Discussionsupporting
confidence: 94%
“…Gaissert et al9 compared the survival outcomes between 101 patients with ACCs and 90 patients with SCCs and found that the prognosis of ACCs was significantly superior to SCCs (5-year OS 52% vs. 39%, P <0.001). Another study based on oriental populations35 also suggested an approximately twofold 5-year survival rate disparity between these two subtypes. In our study, SCCs were more likely to present with local extension, as well as lymph node metastasis, than ACCs at diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies in different parts of the world have shown that resection extends the survival of patients with ACC [3,5,8,9,[13][14][15][16][17]. In our ACCs, the resected group had a significantly longer survival as well.…”
Section: Discussionmentioning
confidence: 55%